Mapping the links between problematic smartphone use, exercise procrastination, and self-control: a network analysis - Yingjuan He; Jie Wen; Fei Liu; Chengming Zhou; Qian Pan; Xiaomin Qin; Miao Miao (BMC Psychology)
Abstract Background Health risk behaviors, such as problematic smartphone use (PSU) and insufficient physical exercise, are prevalent among university students. This study focused on medical students, given that health risk behaviors may impact their health and future career performance. Specifically, the study aimed to explore the relationship between PSU, exercise procrastination, and their shared common risk factor—self-control—using network analysis. Methods A total of 917 undergraduate students (M age = 19.23 ± 1.18 years, 63.58% female) completed the Smartphone Addiction Scale-Short Version, Procrastination in Exercise Scale, and Brief Self-Control Scale. Network analysis was used to examine the associations between PSU, exercise procrastination, and self-control at the item level. Results PSU, exercise procrastination, and self-control formed a stable network structure and were significantly correlated. Specifically, PSU and exercise procrastination were positively associated and both showed significant negative associations with self-control. Self-control may serve as an intermediary bridge between PSU and exercise procrastination. Conclusion In the future, interventions targeting self-control may effectively reduce PSU and exercise procrastination behaviors while promoting adherence to healthy behaviors among medical students.